Creation of Learning Strategies for Development of English Reading Skill by the Extensive Reading in EFL Classroom - Wutthisingchai , Sajeerat (Asian Journal of Education and Training, 2022)
The research aimed to develop the reading process and comprehension through extensive reading of 30 English major freshmen students conducted at Lampang Rajabhat University, Thailand, in the academic year of 2018. Data was collected by using pre-and post-test. Several follow-up activities and guidelines, including formative and summative assessments, were also conducted. Moreover, the study also surveyed the coursework book at the end of the semester, which promotes learning strategies through comprehension questions of pre-and post-activities in class throughout the whole semester. All comprehension tests were valued in descriptive statistics, and the paired sample t-test was analyzed by SPSS Statistics in the study. Based on the statistical data, the overall results revealed that pre-and post-test had significant differences in scores at the level 0.01, which means that the post-test scores were significantly higher than the pre-test scores. Further results were evaluated through qualitative measures including further discussion and conclusion.